A SMART-complex quality diagnostic criteria for future skilled workers professional training - Zuieva, Alona (Professional Pedagogics, 2018)
Taking into account the importance of future skilled workers training in accordance with production technologies level the need for developing and using latest technologies in professional industrial training process is updated. The SMART-complex is defined as a complex informational dynamic system of a certain teaching-methodical direction that meets the specific criteria. They are areas of practice, measurable, achievable, relevant and time-bound. It is essential that SMART complex has static, dynamic and environment components. It provides integral information about a study subject with the possibility of prompt access to educational content via Internet, provides rapid assessment of educational activities by trainees. SMART-complex is supported by all commonly used modern devices. SMART- complex operates with the most common types of modern multimedia content. In SMART complex, such e-learning resources can be located and functionally interconnected to distance education system, multimedia content, digital textbooks, cloud resources, etc. It is described that the learning process with SMART-complex has flexible and/or blended learning features. It also may include a system of distance learning. The relevance of fuzzy logic methods for measuring the qualitative characteristics of SMART complex is pointed out. The criteria for quality diagnosing of SMART-complex for future skilled workers professional training are presented. They are content, attestation, supportive, adaptive and communicative. It was emphasized on the need for further detailing the quality diagnosis factors for SMART-complex and their expert assessment.